Cultural and social influences on Saudi family travel decisions: A systematic-quantitative synthesis for enhancing domestic tourism competitiveness in the face of international tourism - Abdelghani , Abdelrahman A. A.; Fayyad , Sameh; Al-Romeedy, Bassam Samir; Ahmed , Hebatallah A. M. (Research Journal in Advanced Humanities, 2025)
This research analyzes the cultural and sociological elements affecting Saudi family travel choices (FTD) and their implications for domestic tourist competitiveness (DTC) amid global competition. Employing a mixed-methods approach—combining a systematic literature review (SLR) with partial least squares structural equation modeling (PLS-SEM) on data from 469 Saudi respondents—the research reveals that cultural influences (β = 0.452) and social influences (β = 0.338) significantly drive FTD, which in turn enhances DTC (β = 0.427). Direct impacts of cultural (β = 0.208) and social elements (β = 0.213) on DTC were also significant, whereas foreign tourism allure adversely moderates the FTD-DTC link (β = -0.106). The research correlates with Saudi Arabia’s Vision 2030 and Sustainable Development Goals (SDGs), notably SDG 8 (economic development), SDG 11 (sustainable communities), SDG 12 (responsible consumerism), and SDG 5 (women equality). Practical options include using Halal tourism, AI-driven marketing, and gender-inclusive regulations to boost local competitiveness while protecting cultural identity.